Medical Students as Health Educators at a Student-Run Free Clinic: Improving the Clinical Outcomes of Diabetic Patients - Gorrindo, Phillip (Acad Med, 2014)
PURPOSE: Student-run free clinics (SRFCs) provide service–learning opportunities for medical students and care to underserved patients. Few published studies, however, support that they provide high-quality care. In this study, the authors examined the clinical impact of a medical student health educator program for diabetic patients at an SRFC. METHOD: In 2012, the authors retrospectively reviewed the electronic medical records of diabetic patients who established care at Shade Tree Clinic in Nashville, Tennessee, between 2008 and 2011. They compared clinical outcomes at initial presentation to the clinic and 12 months later. They analyzed the relationship between the number of patient–student interactions (touchpoints) and change in hemoglobin A1c values between these two time points and compared the quality of care provided to best-practice benchmarks (process and outcomes measures). RESULTS: The authors studied data from 45 patients. Mean hemoglobin A1c values improved significantly from 9.6 to 7.9, after a mean of 12.5 ± 1.5 months (P < .0001). A trend emerged between increased number of touchpoints and improvement in A1c values (r(2) = 0.06, P = .10). A high percentage of patients were screened during clinic visits, whereas a low to moderate percentage met benchmarks for A1c, LDL, and blood pressure levels. CONCLUSIONS: These findings demonstrate that a medical student health educator program at an SRFC can provide high-quality diabetes care and facilitate clinical improvement one year after enrollment, despite inherent difficulties in caring for underserved patients. Future studies should examine the educational and clinical value of care provided at SRFCs.